Фантасмагория, или Сказки третьего тысячелетия: повести / Александр Романов - Романов Александр Анатольевич (ЛУч, 2011)
Экземпляры: ф. 2 (20120629) / Инвентарный номер: 98781 / Цена: 230.08 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 69 / ББК: 84(2Рос=Рус)6